Penerapan Arsitektur Kontemporer pada Kawasan Bisnis Art Exhibition of Anime di Kota Tangerang - Nabilla Tania Kusuma Wardani; Dody Kurniawan; Putri Suryandari (MAESTRO, 2022)
The population of anime lovers in Indonesia ranks third in the world after El Savador and the Philippines. These anime lovers not only like to watch anime but they also have a consumptive nature towards anime specialties or Japanese cuisine. In addition, contemporary art exhibition tourist attractions are also being favored by the public as a place to unwind and travel in the Capital City area. With the design of the Exhibition building in Tangerang City, it is hoped that it can be a place for artists to exhibit their contemporary artworks and anime lovers in channeling their talents and creativity. The application of contemporary architectural concepts is expected to give a more expressive building impression and provide a hierarchy of comfort to visitors. Keywords : Anime Lovers, Contemporary Architecture, Tangerang City